2016
DOI: 10.1097/md.0000000000002746
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Sacral Angle and Vertical Angle of Sacral Curvature and Lumbar Disc Degeneration

Abstract: The purpose of this study is to determine the reliability and validity of a goniometric measurement of the vertical angle of the sacrum and sacral angle (SA), and their relationships to lumbar degeneration.A herniated lumbar disc is one of the most frequent medical issues. Investigators in a number of studies have reported associated risk factors for prevalent disc degeneration. Atypical lumbosacral angles and curvature are thought to contribute to the degradation of the spine by many researchers. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Concentrated rehabilitation has shown at least 16% decrease in pain and also delivers mild profits in avoiding advance deformity (28,29). Bracing is the real management for SK, nonetheless, the distress is that its consequences might not be long-lasting deprived of continuing bracing.…”
Section: Nonsurgical Conservative Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Concentrated rehabilitation has shown at least 16% decrease in pain and also delivers mild profits in avoiding advance deformity (28,29). Bracing is the real management for SK, nonetheless, the distress is that its consequences might not be long-lasting deprived of continuing bracing.…”
Section: Nonsurgical Conservative Measuresmentioning
confidence: 99%
“…Hyperextension images of above a bolster on the apex of the kyphosis are essential for evaluating the degree of curve flexibility (27,28). Computerized Tomography scan is useful in bony structures diagnosis and measurement of spine angles and pedicle dimensions before surgery (29,30). Some studies showed the severity of thoracic kyphosis is not essentially associated with neurological utility (31).…”
Section: Imaging Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cobb method is used to measure the magnitude of the coronal deformity [28,29]. CT scan is useful for bony abnormalities and spinal canal and pedicular dimensions especially before surgery [30,31]. MRI needs to be taken to envision any occurrence of canal stenosis, facet hypertrophy, pedicular abnormality, foraminal stenosis, and degenerative disc disease [32][33][34][35].…”
Section: Imagingmentioning
confidence: 99%